A CHALLENGING CASE OF FAMILIAL HYPOCALCIURIC HYPERCALCEMIA CONCEALED BY CONCOMITANT VITAMIN D DEFICIENCY AND PAPILLARY THYROID CARCINOMA - Devaraja, Vanusha; Redzuan, Shazatul Reza Mohd; Rajoo, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Familial hypocalciuric hypercalcemia (FHH) is a rare autosomal-dominant disorder resulting from an inactivating mutation in the calcium-sensing receptor (CASR) gene. It is generally benign and characterized by longstanding parathyroid hormone (PTH) - dependent hypercalcemia. Resection of the parathyroid tissue does not normalize serum calcium. CASE We report a case of FHH with evaluation confounded by vitamin D deficiency and newly diagnosed papillary thyroid carcinoma. A 63-year-old female was incidentally noted to have hypercalcemia with elevated PTH during admission for pneumonia. She had completed antituberculosis therapy for gastrointestinal tuberculosis 2 years ago. The baseline vitamin D level was 24nmol/L (NV: 75-100), and the 24-hour urine calcium creatinine ratio was 0.01. Bone mineral density revealed an osteopenic spine. Focused parathyroidectomy was performed after technetium (99mTc) sestamibi SPECT scan which revealed a left superior parathyroid adenoma. However, the calcium levels remained elevated. Histopathological examination of the postoperative sample revealed a metastatic papillary thyroid carcinoma in the lymph node. Hence, she underwent total thyroidectomy, left modified neck dissection, and total parathyroidectomy with auto-transplantation of parathyroid tissue into the presternal space. Albeit that, the serum calcium and PTH remained elevated. PTH-related protein (PTHrP) and 1,25 hydroxy vitamin D levels were within normal range. Opportunistic screening of her daughter revealed that she had raised calcium levels with inappropriately normal PTH and 24-hour urinary calcium creatinine ratio of less than 0.01. The patient’s repeated 24-hour urinary calcium creatinine ratio after repletion of vitamin D was also less than 0.01. We diagnosed her with FHH based on positive family screening and longstanding asymptomatic PTHdependent hypercalcemia refractory to parathyroidectomy. CONCLUSION Our case highlights the diagnostic dilemmas in hypercalcemia, the importance of screening family members and the repetition of 24-hour urine calcium creatinine ratio after correction of vitamin D deficiency.